Converts of Conviction Faith and Scepticism in Nineteenth Century European Jewish Society - Ruderman , David B. (Studies and Texts in Scepticism, 2017)
The series Studies and Texts in Scepticism contains monographs, translations, and collected essays exploring scepticism in its dual manifestation as a purely philosophical tradition and as a set of sceptical strategies, concepts, and attitudes in the cultural field - especially in religions, perhaps most notably in Judaism. In such cultural contexts scepticism manifests as a critical attitude towards different dimensions and systems of secular or revealed knowledge and towards religious and political authorities. It is not merely an intellectual or theoretical worldview, but a critical form of life that expresses itself in such diverse phenomena as religion, literature, and society.